Dictionary-Based, Clustered Sparse Representation for Hyperspectral Image Classification - Zhen-tao Qin; Wu-nian Yang; Ru Yang; Xiang-yu Zhao; Teng-jiao Yang (Journal of Spectroscopy)
This paper presents a new, dictionary-based method for hyperspectral image classification, which incorporates both spectral and contextual characteristics of a sample clustered to obtain a dictionary of each pixel. The resulting pixels display a common sparsity pattern in identical clustered groups. We calculated the image’s sparse coefficients using the dictionary approach, which generated the sparse representation features of the remote sensing images. The sparse coefficients are then used to classify the hyperspectral images via a linear SVM. Experiments show that our proposed method of dictionary-based, clustered sparse coefficients can create better representations of hyperspectral images, with a greater overall accuracy and a Kappa coefficient.